2009
DOI: 10.1037/a0013877
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–behavioral therapy versus usual clinical care for youth depression: An initial test of transportability to community clinics and clinicians.

Abstract: Community clinic therapists were randomized to (a) brief training and supervision in CBT for youth depression or (b) usual care (UC). The therapists treated 57 youths (56% girls), aged 8-15, 33% Caucasian, 26% African-American, and 26% Latino; most youths were from low-income families; all had DSM-IV depressive disorders (plus multiple comorbiditities). All youths were randomized to CBT or UC and treated until normal termination. Session coding showed more use of CBT by CBT therapists, more psychodynamic and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

7
3

Authors

Journals

citations
Cited by 190 publications
(167 citation statements)
references
References 73 publications
7
160
0
Order By: Relevance
“…First, it is ideal for the new generation of methods for modeling change during treatment (e.g., Raudenbush & Bryk, 2002). Second, improvement occurring early in treatment (e.g., Ilardi & Craighead, 1994) may Youth Top Problems 6 go undetected by measurement approaches delivered at post-treatment only, which may in turn increase Type II error in tests of group differences (see e.g., Weisz et al, 2009). Third, increased use of effectiveness designs that pit time-limited evidence-based treatments against usual care of uncontrolled length (see Weisz, Jensen-Doss, & Hawley, 2006), with group differences in treatment dose and duration highly likely, make slope across multiple assessment points a more sensitive index of outcome than post-treatment measurement alone.…”
Section: Youth Top Problemsmentioning
confidence: 99%
“…First, it is ideal for the new generation of methods for modeling change during treatment (e.g., Raudenbush & Bryk, 2002). Second, improvement occurring early in treatment (e.g., Ilardi & Craighead, 1994) may Youth Top Problems 6 go undetected by measurement approaches delivered at post-treatment only, which may in turn increase Type II error in tests of group differences (see e.g., Weisz et al, 2009). Third, increased use of effectiveness designs that pit time-limited evidence-based treatments against usual care of uncontrolled length (see Weisz, Jensen-Doss, & Hawley, 2006), with group differences in treatment dose and duration highly likely, make slope across multiple assessment points a more sensitive index of outcome than post-treatment measurement alone.…”
Section: Youth Top Problemsmentioning
confidence: 99%
“…An additional effectiveness trial feature for which we have argued (Weisz & Gray, 2008;Weisz et al, 2006) is random assignment of clients to the EBP being tested vs. representative usual care; this addresses the critical question of whether the EBP actually improves outcomes relative to the intervention that is normally provided in the absence of the EBP. There is a growing body of effectiveness trial evidence with an array of Science and Practice of Dissemination and Implementation 15 treated problems and disorders and across a broad client age range (e.g., Addis et al, 2004;Weisz et al, 2009). In general, those effectiveness trials in which EBPs are tested against usual care have shown the effect size drop-off described in our earlier section on the implementation cliff.…”
Section: Dis: Some Current Directions In Dissemination and Implementamentioning
confidence: 99%
“…We have participated in this movement, but along the way we encountered 'an inconvenient truth': Treatments that fare well in traditional RCTs do not always seem quite so strong when implemented in everyday clinical practice. We heard this in conversations with practitioners, and we found it to be true in our own effectiveness trials testing cognitive behavioral therapy (CBT) for anxiety and for depression against usual clinical care in youth community mental health clinics [Southam-Gerow et al, 2010;Weisz et al, 2009]. We also conducted 2 meta-analyses of RCTs that had tested youth ESTs in more clinically representative contexts, pitting the ESTs against usual care [Weisz et al, 2006.…”
Section: Implementation Challengesmentioning
confidence: 99%